Papel da pós-graduação no desenvolvimento de competências: um trabalho sob a óptica dos mestres em administração - Nogueira, Maira Vasconcelos (2007)
During the past decades, work marketplace has been suffering significant changes. In this sense, the creation of a new scenario brings relationship transformations between people, their career and the search for continuing development. This research has as its objective identify if any relationship can be observed between Master degree achievements (stricto sensu mode) and the development of competences, verifying how is this connection. On that matter, the intention of the research is to inquire which paper the academic Master degree has developing the competences of the egresses. As for the methodology, the study consists of a descriptive and investigative research. The work is based on the survey of the referring bibliography to the main subject, the question of competences, and the explanation of the universe in which the subject is investigated, the Master degree stricto sensu. The field research was carried through with the Masters for the Mastering in Administration program from Pontifícia Universidade Católica de São Paulo, who had gotten a degree in last the six years. Through research, the personal, academic and professional profile of the egresses was traced, as well collected their perception about how this after-graduation studies had influenced the development of competences. Based on the data raised in the study, it was evidenced that the option for the Master degree is strongly motivated by the seek for more knowledge and for personal accomplishment. Among the competences and knowledge analyzed, the know how to learn and learn to learn was perceived by the egresses as one of the most relevant and the most developed during the course. As for the activities of the course that had collaborated more for this process of development, the experience acquired with the research appeared in promine